Intermittent Hepatic Vein Balloon Occlusion During Radiofrequency Ablation in the Liver - Sudheendra, Deepak (2006)
The purpose of the study was to assess the feasibility of intermittent hepatic vein balloon occlusion during percutaneous radiofrequency (RF) ablation. Eight non-anticoagulated patients who had primary (n = 2) and metastatic (n = 6) liver tumors with a mean diameter of 4.2 cm (range 2.4–6.5 cm) were treated, resulting in a mean ablation diameter of 6.3 cm (range 4.3–9.3 cm). Six of 9 (67%) of the balloon-occluded hepatic veins were patent. No clinical sequelae of thrombosis were noted. Mean length of follow-up with CT and/or MRI was 12 months. Local tumor control was achieved in 5 of 8 patients. Intermittent hepatic vein balloon occlusion could potentially be a low-risk adjunctive maneuver for thermal ablation therapy in the treatment of large tumors and tumors adjacent to large vessels.